Abnormalities of T cells in systemic lupus erythematosus: new insights in pathogenesis and therapeutic strategies. Issue 132 (October 2022) - Li, Hao; Boulougoura, Afroditi; Endo, Yushiro; Tsokos, George C.
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by loss of immune tolerance and sustained production of autoantibodies. Multiple and profound T cell abnormalities in SLE are intertwined with disease expression. Both numerical and functional disturbances have been reported in main CD4 + T helper cell subsets including Th1, Th2, Th17, regulatory, and follicular helper cells. SLE CD4 + T cells are known to provide help to B cells, produce excessive IL-17 but insufficient IL-2, and infiltrate tissues. In the absence of sufficient amounts of IL-2, regulatory T cells, do not function properly to constrain inflammation. A complicated series of early signaling defects and aberrant activation of kinases and phosphatases result in complex cell phenotypes by altering the metabolic profile and the epigenetic landscape. All main metabolic pathways including glycolysis, glutaminolysis and oxidative phosphorylation are altered in T cells from lupus prone mice and patients with SLE. SLE CD8 + cytotoxic T cells display reduced cytolytic activity which accounts for higher rates of infection and the sustenance of autoimmunity. Further, CD8 + T cells in the context of rheumatic diseases lose the expression of CD8, acquire IL-17 + CD4 − CD8 − double negative T (DNT) cell phenotype and infiltrate tissues. Herein we present an update on these T cell abnormalities along with underlying mechanisms and discuss how these advances can be exploited therapeutically. Novel strategies to correct these aberrations in T cells show promise for SLE treatment.